(untitled) (Medical Forum Monthly, 2022)
Objective: To determine the frequency of pattern of bacterial isolates in children with thoracic empyema visiting to Children Hospital Larkana, Sindh. Study Design: Cross sectional Descriptive Study Place and Duration of Study: This study was conducted at the Department of Paediatric Medicine, Children Hospital CMC (H), SMBBMU, Larkana, Sindh, Pakistan from September, 2020 to March, 2021 for a period of six months. Materials and Methods: All patients who implemented the inclusion criteria and admitted in Children Hospital CMC (H), Larkana were took in the study. The procedure, its risks and benefits of the study enlightened and then informed consent was received. Chest x-rays were taken in all patients at the time of admission, after intercostal tube drain (ICTD) introduction, its removal and at discharge, while ultrasound CT of chest were done when needed. Diagnostic thoracentesis was performed and pleural fluid was submitted for biochemical analysis (total and differential leukocyte count, protein, sugar, and LDH) and microscopic analysis (Gram staining, culture, and smear for AFB and Gen Expert). Outcome variable i.e. pattern of bacterial isolates was assessed. All the collected data were recorded into the proforma added towards the end and used electronically for research purpose. Results: Mean ± SD of age was 5.1±2.3 years. Out of 128 patients, 77 (60.2%) were male while 51 (39.8%) were female. In distribution for pattern of bacterial isolates, staphylococcus aureus were noted in 23 (18%) patients, staphylococcus epidermidis was noted in 17 (13.5%), streptococcus pneumoniae was noted in 14 (10.9%), 09 (7%) had pseudomonas, 09 (7%) had Klebsiella pneumoniae, proteus in 5 (3.9%), E.coli in 4 (3.1%), 4 (3.1%) had mixed, tuberculosis was noted in 18 (14%) while 25 (19.5%) patients had no growth pattern of bacterial isolates. Conclusion: It is to be concluded that staphylococcus aureus was the commonest organisms of bacterial isolates followed by mycobacterium tuberculosis in our study. Further research is required to better understand the factors associated with pattern of bacterial isolates in children with thoracic empyema.